2019
DOI: 10.1002/jcla.23054
|View full text |Cite
|
Sign up to set email alerts
|

Novel SPEG variant cause centronuclear myopathy in China

Abstract: Background Centronuclear myopathy (CNM), a subtype of congenital myopathy (CM), is a group of clinical and genetically heterogeneous muscle disorders. Centronuclear myopathy is a kind of disease difficult to diagnose due to its genetic diversity. Since the discovery of the SPEG gene and disease‐causing variants, only a few additional patients have been reported. Methods A radiograph test, ultrasonic test, and biochemical tests were applied to clinical diagnosis of CNM. We performed trio medical exome sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…The reported SPEG gene variants are all related to CNM. A total of 16 variant sites have been reported including the two sites we discovered in our study as shown in Table 1 [10,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The reported SPEG gene variants are all related to CNM. A total of 16 variant sites have been reported including the two sites we discovered in our study as shown in Table 1 [10,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Underlying these clinical phenotypes, cellular and molecular hallmarks of CNM include increased central nucleation of myofibers and variation in myofibers size, and disruptions in triadic structure and E-C coupling [ 10 , 44 , 45 ]. To date, 20 patients have been identified with SPEG mutations [ 23 , 44 , 46 , 47 , 48 , 49 ]. Figure 1 shows the location and mutation type of all reported SPEG variants.…”
Section: Speg Mutations In Myopathies and Cardiomyopathiesmentioning
confidence: 99%
“…Mutations affecting both SPEG isoforms are associated with more severe clinical and molecular phenotypes than those that spare SPEG α, the shorter isoform lacking amino acids 1-854 [ 8 ]. Of the eight patients shown to carry mutations affecting both SPEG α and SPEG β, all demonstrated cardiac dysfunction, five experienced early death, and one requires constant mechanical ventilation due to severe respiratory problems [ 8 , 43 , 44 , 46 , 51 ]. Mutations affecting only SPEG β are associated with a milder phenotype without cardiac involvement [ 43 , 44 , 50 ], indicating that SPEGα is critical for both skeletal and cardiac function and may be able to partially compensate for SPEGβ loss-of-function.…”
Section: Speg Mutations In Myopathies and Cardiomyopathiesmentioning
confidence: 99%
“…Mutations in genes such as MTM1, DNM2, BIN1, RYR1, CACNA1S, and TTN have been identified for about 60-80% of patients with CNM. In recent studies, the mutations in the SPEG gene (striated muscle preferentially expressed protein kinase) have been associated with CNM in a small case series (3)(4)(5)(6)(7). Herein, we report a case of CM due to a novel variation in the SPEG gene, which is manifested by intellectual disability, a new clinical finding.…”
mentioning
confidence: 90%